STUDI DRAINASE RUAS JALAN TALISAYAN SEKITAR JEMBATAN SUNGAI SAKA KECAMATAN SAMBALIUNG KABUPATEN BERAU - TRIDIYANTO, DEDIK (KURVA S JURNAL MAHASISWA, 2014)
Drainage that comes from the English language that has meaning siphon drainage , drain , remove, or divert water . Generally , drainage may be defined as technical measures to reduce excess water , whether from rain , seepage , or excess irrigation water from an area or land , so that the function of land or areas are not disturbed .              Benefits of the drainage system are formation of a drainage system that can distribute and absorb water at the bridge , oprit bridge and around the river bridge Saka in Talisayan Street Berau district of addition to protect the road , especially oprit from the adverse effects of water to the strength and stability of the building .              Based on the results of the drainage analysis can be concluded ; U -shaped cross section of the water channel is made of reinforced concrete pair , in Region 1 ( D1 ) left and right side of the road Talisayan with the discharge water channels ( Q1 ) = 0.6192 m3 / sec , the dimensions of the channel is High ( h ) = 100 cm , Width ( b ) = 84 cm , length of the water channel ( L ) = 900 x 2 = 1,800 m . Region 2 ( D2 ) to the left and right side of the road Talisayan with the discharge water channels ( Q2 ) = 0.7799 m3 / sec , the dimensions of the channel is High ( h ) = 100 cm , width ( b ) = 92 cm , length of waterways ( L ) = 1600 x 2 = 3200m . Based on the recapitulation of the estimated price for the drainage work Talisayan Street Berau district obtained total drainage works price plus VAT ( VAT ) of 10% amounting to Rp . 2.076.231.597.00